URGENCY OF EMERGENCY CONSTITUTIONAL LEGAL PERSPECTIVE IN LEGAL SYSTEM PRACTICE IN INDONESIA - Arief Fahmi Lubis (International Forum of Researchers and Lecturers, 2023)
Danger or nood can occur anytime and anywhere, in this case, it can only occur in a certain area or it can even occur as a whole in the territory of a country.The purpose of this research is to give an idea that emergency constitutional law provides reasons or the basis for granting the state a right to take action in overcoming or dealing with dangerous situations.This qualitative research used a descriptive approach to collect data systematically, factually, and quickly according to the description when the research was conducted. The results of this study indicate that it is necessary to stipulate an emergency law that regulates matters of governance that due to urgent circumstances need to be regulated immediately.